Disturbance observer assisted robust control of wing rock motion based on contraction theory. (September 2013) - Kuperman, Alon; Zhong, Qing-Chang
A nonlinear robust control strategy is proposed in this paper to deal with wing rock motion. The method is based on the disturbance observer enforced contraction theory results. The disturbance observer calculates and robustly cancels system uncertainties and input disturbances. The information regarding the known part of the nonlinear plant dynamics is used by the controller, while the uncertainties and disturbances are treated as an additional input to the system and dealt with by the disturbance observer. The algorithm demonstrates good performance in damping the oscillations while rejecting the disturbances. Simulations are provided to demonstrate the effectiveness of the proposed method via an application to an experimentally derived delta wing rock model operating in both nominal and uncertain environments.